Drivers' response to the sign 'Sutthisan Road keep left' at Huey Kwang interchange, Princess Vipavadi Rangsit Highway, Thailand - Huang, Min-zen; Jones, John Hugh; Prapansak Burunaprapa; Yordphol Tanaboriboon; R.O.C Government (Bangkok : Asian Institute of Technology, 1981)
For the sake of finding the drivers' response to a highway sign react in g SUTTHISAN ROAD KE EP LEFT, installed 3 00 meters upstream from the northbound. exit ramp of the Huey kwang Interchange on the Princess Vipavadi Rangsity Highway, Bangkok, a before-and-after study was conducted. Two experimental signs of different dimensions were successively installed and tested. The traffic data were obtained by video-tape recording. Principal component analysis was used to find the main factors that describe the traffic characteristics. Canonical correlation analysis was then used to find the relationship between the sign-affected factors and the objective condition factors. The t-test was used to find the differences in traffic characteristics before and after the signs were installed. It was found that the higher the percentage of total volume being trucks or buses, the higher would be the erratic maneuver rate. The installation of the experimental signs significantly decreased this rate. The weather, and the size of the sign are other important factors that affect the drivers' response. The traffic volume, the days of the week, the time of day, and the exit traffic volume were found not to be important.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1981
Keywords: Traffic signs and signals -- Thailand -- Vipawadi Rangsit Highway